2022
DOI: 10.3390/math10173146
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Emergency Evacuation Route Planning Model Based on Fire Prediction Data

Abstract: For the emergency evacuation of cruise ships in case of sudden fire, this research proposes a dynamic route optimization method based on the improved A* algorithm for real-time information, in order to obtain the real-time optimal evacuation route. Initially, a basic network topology diagram is established according to the internal structure of the cruise ship. Before the occurrence of the accident, the A* algorithm can be applied to obtain an a priori evacuation network consisting of all the optimal routes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…(2023) [6], Song et al (2021) [7], Shih & Tsai (2023) [8], and Hou et al (2021) [9]. Calculation and modeling of probable scenarios for the development of a fire at a cultural heritage site will allow us to determine the risk to people and structures of objects and select the most effective fire protection systems for building structures from such works as Hou et al (2021) [9], Shaham & Benenson (2018) [10], and Deng et al (2022) [11].…”
Section: Garcia-castillo Et Al (2023)mentioning
confidence: 99%
See 1 more Smart Citation
“…(2023) [6], Song et al (2021) [7], Shih & Tsai (2023) [8], and Hou et al (2021) [9]. Calculation and modeling of probable scenarios for the development of a fire at a cultural heritage site will allow us to determine the risk to people and structures of objects and select the most effective fire protection systems for building structures from such works as Hou et al (2021) [9], Shaham & Benenson (2018) [10], and Deng et al (2022) [11].…”
Section: Garcia-castillo Et Al (2023)mentioning
confidence: 99%
“…Shih et al (2023) [8], Hou et al (2021) [9], Shaham & Benenson. (2018) [10], Deng et al (2022) [11], and Hvozd et al (2021) [12] revealed that the determination of the level of fire safety should be carried out for the conditions of free development of the fire. However, in addition to ensuring the safe evacuation of people, it is also necessary to ensure the regulatory limits of fire resistance of building structures.…”
Section: Introductionmentioning
confidence: 99%
“…Hui Zhang, Tao Chen, and Peter B Luh conduct related research in a team manner. The stair evacuation with considering evacuees' walk preferences is the outstanding contribution in fire safety evacuation of these scholars [28]. Evacuees' walk preference and psychology are introduced into a cellular automata (CA) model, and validation of the model is proved by two fire drills in two high-rise buildings.…”
Section: Network Of Authorshipsmentioning
confidence: 99%
“…Scientometric research has been used in numerous different scientific fields to provide information or data such as computer vision applications for construction [14], safety science community [15], smart disaster management [16], microalgae-based wastewater treatment [17], computational modelling in built environments [18], dynamics applications in construction management [19], AAP (accident analysis and prevention) [20], CEM (construction engineering and management) [21], or BIM (building information model) [22]. The findings based on scientometric analysis provide excellent research status and development trends for researchers in particular domains of scientific inquiry [23][24][25][26][27][28][29]. Researchers can gain quantitative insights in the development direction and efficiently solve complex problems with respect to the theoretical backgrounds, tools, and frameworks on particular domains of scientific inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…In such situations, individuals inside the building may not be aware of suitable evacuation routes, especially when facing unexpected events such as fires, tsunamis, or hurricanes. It is crucial to swiftly move occupants to safe areas to minimize potential damage and effectively manage emergency situations [1]. Therefore, planning navigation for optimal evacuation routes can reduce the likelihood of property damage, control congestion during emergencies, and shorten evacuation times to ensure that inhabitants can be safely and efficiently evacuated, ultimately saving more lives [2]- [4].…”
Section: Introductionmentioning
confidence: 99%